PENGARUH TERPAAN MEDIA SOSIAL AKUN INSTAGRAM @KULINERPKU TERHADAP KEBUTUHAN INFORMASI KULINER - Melya Wati; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
In this modern era, Instagram is a social media that can make it easier for people to find culinary information quickly. The easy way to use the Instagram application makes users use Instagram as a medium of information to meet their needs. One of the accounts that utilizes Instagram social media as a medium for spreading information about the culinary city of Pekanbaru is @kulinerpku. This study aims to determine how much influence social media exposure has on fulfilling the culinary information needs of followers of the @kulinerpku Instagram account. This study uses the theory of SOR (Stimulus, Organism, Response) as a basis for research testing. This study used a quantitative explanatory research method with a sampling technique in this study using random sampling and using the slovin formula which obtained a total of 277 respondents from the 488 thousand population of followers @kulinerpku. The data collection technique uses a questionnaire which is then tested for validity and reliability. The data analysis technique in this study was a simple linear regression test and a determination test which was calculated using the SPSS for windows. Based on the results of simple linear regression analysis, the coefficient value in this study is Y = 5.173 + 0.830X. Meanwhile tcount (22.018) is greater than t table (4.448). Where Ho is rejected and Ha is accepted with a significance of 0.000, it can be concluded that there is a large influence between exposure to social media on fulfilling culinary information needs on followers of the Instagram account @kulinerpku with an influence of 63.8% which is categorized as strong. Keywords : Media Exposure, Information Needs